Research progress on influencing factors and control methods of slagging in biomass combustion - Jiyi Luan; Qi Wang; Dongwei Shao; Bo Cui; Ping Han; Qiang He (Frontiers in Energy Research)
Biomass combustion serves as a carbon-neutral energy solution but faces persistent challenges due to ash-related operational inefficiencies. This review systematically examines the thermochemical interactions among alkali metals (K, Na), chlorine (Cl), and sulfur (S) in biomass ash systems, elucidating their synergistic contributions to deposition mechanisms while evaluating mitigation approaches. KCl volatilization-condensation dominates in high-chlorine feedstocks (agricultural residues), whereas sulfates control ash deposition in lignocellulosic biomass. Bed agglomeration mechanisms stem from alkali silicate eutectics with depressed melting points (K2O·nSiO2), while chloride-induced degradation of protective oxide layers initiates metallic corrosion. Comprehensive assessment of mitigation techniques reveals aluminosilicate additives (kaolin) outperform conventional pretreatment methods (aqueous and acid leaching), achieving ash fusion temperature elevation beyond 1,300°C through interfacial reactions generating refractory kalsilite (KAlSiO4). The synthesis demonstrates that hybrid strategies combining fuel-specific preprocessing with optimized additive formulations produce synergistic mitigation effects. These insights provide mechanistic understanding essential for optimizing combustion system durability, while highlighting unresolved challenges in fuel-additive compatibility, additive stability under thermal cycling, and advanced corrosion-resistant material development.